Save Our Film campaign. - Goh, Zhi Ling. (2010)
The 'Save Our Film' Campaign is a pioneering public communications initiative aimed at raising awareness amongst youths of Singapore's rich film heritage and the need to save it for our future. It was conceptualized and implemented by the project team for local charity Asian Film Archive for their 2010 fifth anniversary celebrations. The campaign produced the first pool of data on film attitudes in Singapore obtained through surveying over 300 respondents online and conducting focus groups and interviews with film community members. This data would inform the development of future plans regarding local film heritage, marketing, and even production, which areas are pertinent to Singapore's outlined media agenda. A media strategy utilising online social media platforms coupled with a series of guerilla marketing efforts upholding the core themes of films holding our memories and seeding inter-generational conversations were then carried out over the month-long run, including displaying posters and DVDs promoting early lost films island-wide, impromptu text projections of key messages in malls, and a final roving showcase featuring local film memories drawn from the film community and public down Orchard Road. These served as economical, engaging and experiential advertisements for the cause that delivered concise and unusual points of information for the public to encounter in an unexpected but memorable way.